Penilaian Kinerja Bidan Alumni Akademi Kebidanan Yogyakarta Di Kabupaten Sorong Selatan - Eka Nur Rahayu (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: South Sorong regency as one of the districts in the province of West Papua is highly needed health workers because there shortage of midwives. Yogyakarta Midwifery Academy has been cooperating with the government in the South Sorong regency since 2009 had been educated 38 and in 2012 had been graduated 25 midwives. The graduates have been placed in South Sorong regency as a midwife, 3 midwives working in district general hospitals and the other working in health centers or as midwife in the village.Objective:The research aimed to find out the performance of Yogyakarta Midwifery Academy graduates from South Sorong regency.Method: The study was quantitative and qualitative research with survey by using questionnaire and interview. The research sample was taken purposively that is the alumni represent their workplace in the helath center or hospital including independent practice.Results:In the amount of 27 Yogyakarta Midwifery Academy graduates working in South Sorong regency, 89.9% worked as a midwife and midwife at the health center, 11.1% worked in the hospital. Midwives who work in the hospital was enough get the knowledge about midwifery care, which needs to be added is the introduction of more modern tools such as ultrasound. The performance of Yogyakarta Midwifery Academy graduatesis good enough in carrying out midwifery care and professionalism.Conclusions:The performance of Yogyakarta Midwifery Academy graduateswho work in South Sorong is good. Performance of midwives who work in the health center or midwife should be given the material beyond the competence because of the limitations of the health worker. There is need additional training for graduates in accordance with the placement.Keywords: performance, midwife